Facile synthesis of sulfhydryl modified covalent organic frameworks for high efficient Hg(II) removal from water - Zhiyao Ma; Fuyang Liu; Nengsheng Liu; Liu, Wen; Meiping Tong (Journal of Hazardous Materials, 2021)
In present study, we fabricated sulfhydryl modified covalent organic frameworks (COF-‒SH) through one-step reaction for the removal of Hg(II) from water. Different techniques were employed to characterize the fabricated COFs. We find that COF-‒SH exhibits great adsorption capacity (1283 mg/g) towards Hg(II), which is over 25 times higher than that of COF-1 without ‒–SH (53.1 mg/g). COF‐SH has fast adsorption kinetics with the removal of 95% of 1000 μg/L Hg(II) within 30 min and over 99% after 2 h. Under a wide pH range (from 4 to 9), COF-‒SH exhibits high removal efficiencies (>99%). Moreover, COF‐SH can selectively adsorb Hg(II) in the presence of other metal cations up to 1000 μg/L. X-ray photoelectron spectroscopy analysis reveals the presence of high affinity between thiol-S atom and Hg(II), which is also responsible for the high selectivity towards Hg(II) compared with other cations. Because of the transfer from enol form to keto form during synthesis, COF‐SH exhibit remarkable stability during 10-cycle regeneration and reuse test. During utilization in wastewater extracted from Hg contaminated sludge, COF-‒SH displays high Hg(II) removal efficiency (>95%) under multiple coexisting ions conditions. The results suggest that COF-‒SH have great potential for Hg(II) removal from water under complex conditions.
Keywords: Adsorption; Covalent organic frameworks; Heavy metal removal; mercury; Reusability; Wastewater treatment